Measuring quality of life at work for healthcare and social services workers: A systematic review of available instruments - Wang, Liang; Touré, Moustapha; Poder, Thomas G. (Health Care Science, 2023)
Quality of life at work is an important and widely discussed concept in the literature. Several instruments can be used to measure it, but with regard to healthcare and social services, the existing instruments are not well known. A review of available instruments intending to capture the quality of life of healthcare and social services workers (QoLHSSW) is necessary to better assess their working conditions and promote programs/guidelines to improve these conditions. The aim of this study was to identify the existing instruments used in measuring QoLHSSW and explore their characteristics. Particular attention was given to instruments adapted to the province of Quebec, Canada, which enabled the determination of which instruments are adapted for the measurement of QoLHSSW in Quebec and possibly elsewhere. A systematic review of the literature was conducted according to the JBI methodological guide. The articles' selection procedure was performed according to the PRISMA flowchart. The search was conducted up to October 28, 2021, and then updated on January 25, 2023, in four databases: PsycINFO, Medline, Embase, and CINAHL. The selection and extraction were performed independently by two researchers. The analysis of the quality of the studies was performed with the COnsensus‐based Standards for the selection of health Measurement Instruments. From a total of 8178 entries, 13 articles corresponding to 13 instruments were selected. Among these instruments, the common aspects that were considered were work conditions, job satisfaction, stress at work, relationship/balance, and career development. Most instruments used a 5‐point Likert scale. Various validation methods were used, including reporting Cronbach's alpha for overall scale reliability; factor analysis to test construct validity; different model fit indices to test model superiority; different language comparisons to test cross‐cultural validity; and qualitative expert reviews to assess content validity. Quality of life at work is an important and widely discussed concept in the literature. Several instruments can be used to measure it, but with regard to healthcare and social services, the existing instruments are not well known. A review of available instruments intended to capture the quality of life of healthcare and social services workers is necessary to better assess their working conditions and promote programs/guidelines to improve these conditions.